STUDY OF BINDING AFFINITY OF OLIGOPEPTIDE- BINDING-PROTEIN DOMAIN-A TO BRADYKININ - Erika Rahayu, Anisah
ABC (ATP-binding cassette) transporters are vital to any living system and involved in the translocation of a wide variety of substrates. They are involved in many crucial processes, including nutrient uptake, lipid trafficking, drug and antibiotic excretion, and cell volume regulation. The core component of the ABC transporters is formed by the transmembrane domains (TMDs), together with the nucleotide binding domains (NBDs) and substrate binding domains (SBDs), which all constitute the actual translocator. The SBDs specialize a certain transporter for translocation of a specific substrate. Oligopeptide binding protein (OppA) is an SBD showing an ability of binding various peptides with a length of 4–35 residues. In previous studies, crystal structure of OppA showed open and closed conformation with movement of two protein lobes became nearer allowing to capture the substrate. Despite their well-known stuctures, an OppA molecular model for binding and or transport still remains debated. Therefore, the studies of conformational states and changes of OppA in vitro are required. In the present research, the binding affinity of OppA (Kd value) was determined by the method of ITC (Isothermal Titration Calorimetry), and substrate-bound protein species were determined by the method of ALEX-smFRET (Alternating laser excitation – single molecule fluorescence resonance energy transfer). In both methods, bradykinin (RPPGFSPFR) was used as a substrate, and the binding affinity between OppA and bradykinin under various pH and buffer conditions was determined by both methods. An OppA wild-type was used to observe binding affinity in the ITC method, meanwhile an OppA mutant with position mutation A209C and S441 was used to observe conformational changes in the ALEX-smFRET method. The later, fluorophore as a donor (Alexa555) and acceptor (Alexa647) specifically bound to cysteine OppA mutant. The ITC results showed that Kd values of OppA in KPi buffer pH 7.0 (20 mM KPi pH 7.0, 150 mM NaCl) and in KPi buffer pH 7.4 (50 mM KPi pH 7.0, 150 mM NaCl) were 0.80 and 0.87 µ M, respectively. This showed that the binding affinity of OppA to bradykinin was higher in KPi buffer pH 7.0. On the other hand, ALEX-smFRET results showed that OppA mutant formed aggregate in KPi buffer pH 7.0, but not in pH 7.4. The ALEX-smFRET results also